Deregulation and Competition: Comparison of Regional Aviation Markets in Western Australia - Zhou, Heng (Curtin University, 2020)
In Western Australia, some aviation issues such as air passenger movement decline and high regional airfares have seriously hampered regional public movements and hindered economic growth. Therefore, to assist the transport government tackling these issues, this thesis uses a variety of data and modelling methods to investigate the regional aviation market and the competition in Western Australia, particularly the air travel demand forecasting, regional aviation market exploration and the travel mode and airline choice estimation.